Reading Instruction for Students with Emotional Disturbance: A Mixed-Methods Investigation. Issue 3 (May 2021) - McKenna, John William; Adamson, Reesha; Solis, Michael
Although there is a substantial body of observation research investigating the manner in which reading instruction is provided to students with learning disabilities, there is little research in this area involving students with and at risk for emotional disturbance. The purpose of this investigation was to contribute to the limited corpus of observation studies investigating school-based practice in reading for this student population. In this investigation, 11 teachers from two states were systematically observed while providing reading instruction over the course of the 2017-2018 school year. Participating students were also observed over the course of the year and completed two standardized reading assessments at the beginning and end of this investigation. Teachers were also interviewed to identify contextual factors that promote or impede the provision of high quality reading instruction to this student population. Study findings suggest that teachers are in need of additional training, support, and resources to maximize instructional time. Students in this sample tended to make no or minimal progress in reading and were frequently observed displaying low levels of academic engagement across settings. Implications for school practice and areas for future research are discussed.